ANALISIS PERBEDAAN EFEKTIVITAS BIAYA PENANGANAN GULMA MENGGUNAKAN MULSA PLASTIK DENGAN BAHAN KIMIA AKTIF PADA TANAMAN KELAPA SAWIT (TBM) DI PT.UMADA - Tri Aji Rahmat Taufiq; Badrul Ainy Dalimunthe; Kamsia Dorliana Sitanggang; Khairul Rizal (Fakultas Pertanian, Universitas Janabadra, 2024)
Weed control is usually carried out on oil palm plantations using active chemicals, but on PT. UMADA is trying to use plastic mulch. Therefore, researchers want to analyze the differences in the costs of handling weeds using mulch and active chemicals. This research aims to determine the comparison of the costs of using mulch and active chemicals needed to control weeds in oil palm plantation areas, and how to solve problems regarding weed control in oil palm plantations. This research was conducted in block 6 division I, oil palm plantations PT. Umada, North Sumatra. This research was carried out from 21 September 2022 to 21 September 2023, on the PT UMADA plantation trial land where plastic mulch had been installed covering an area of 1 hectare. Data processing is based on primary data and secondary data obtained from company data. Based on the results of data analysis in the field and variance analysis, it is clear that the cost comparison is very different in the use of mulching and spraying active chemicals. The cost of using active chemicals is IDR 541,000 cheaper than the cost of using plastic mulch of IDR 1,820,000 so it can be concluded that the use of active chemicals is more effective than the use of plastic mulch.Keey-words: active chemicals, cost, immature plants, mulch, weeds